Physical Disabilities - Therapeutic Implications 2017
DOI: 10.5772/intechopen.69051
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Dysfunction in Critical Illness

Abstract: Despite improvements in critical illness survival rates with recent developments in medical care, many patients still have long-term physical disabilities following stays in the intensive care unit (ICU). Critical illness-induced muscle weakness, so-called ICU-acquired weakness (ICU-AW), is a common occurrence in approximately 50% of critically ill patients in the ICU requiring mechanical ventilation for >7 days. ICU-AW contributes to increases in duration of mechanical ventilation and lengths of ICU and hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 164 publications
(187 reference statements)
0
3
0
Order By: Relevance
“…They reported that the intervention markedly improved the 6-min walking distance and lower limb muscle strength on discharge from the hospital. Similarly, Lida et al 22) examined critically ill patients requiring acute care, dividing them into the early (systemic inflammation from days 0 to 5) and late (inactivity after day 5) phases, and noted the necessity of considering appropriate exercise intensity levels in each phase.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the intervention markedly improved the 6-min walking distance and lower limb muscle strength on discharge from the hospital. Similarly, Lida et al 22) examined critically ill patients requiring acute care, dividing them into the early (systemic inflammation from days 0 to 5) and late (inactivity after day 5) phases, and noted the necessity of considering appropriate exercise intensity levels in each phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, medical and circulatory factors were not significantly associated with ADL independence at hospital discharge. Future studies should consider whether low and passive exercise 43 or neuromuscular electrical stimulation 44 can substitute for EM in patients who cannot achieve EM due to medical contraindications or cardiovascular factors. Previous studies have reported that factors related to the medical staff are a major barrier to mobilization [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Most patients in this study may not have been able to tolerate mobilization, consistent with the expert consensus that it is difficult for patients to get out of bed or achieve mobilization during catecholamine therapy. 11 ) In the presence of circulatory instability, the mobilization rates are usually low, and passive exercise, 31 ) cycle ergometer exercise, 32 ) and neuromuscular electrical stimulation 33 ) may be used. Determination of the optimal rehabilitation level and duration before the patient achieves physiological stability should be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%